DEVELOPMENT OF COMIC LEARNING MEDIA ON STUDENT FABLE TEXTS IN JUNIOR HIGH SCHOOL - Adelia, Tantri; Rambe, Riris Nurkholidah (JURNAL KONFIKS, 2025)
In the teaching process, educators are expected to take an active role in adapting and delivering diverse teaching strategies. However, a careful examination of the SMP Islam Setia Nurul Azmi classroom reveals persistent challenges in the implementation of effective instructional methods, primarily attributable to the paucity of instructional media available to the teachers. This shortage has a deleterious effect on student motivation. The objective of this study is to develop comic-based educational media focused on fable texts for seventh-grade students, with the aim of enhancing their writing skills. The research methodology employed a Research and Development (R&D) approach based on the 4-D model by Thiagarajan, comprising the following stages: define, design, develop, and disseminate. Data were collected through expert validations and response questionnaires. The media was rated as highly feasible by media experts (90%), content experts (100%), and linguists (86%). A study of usability assessments revealed high practicality scores from teachers (91%) and students (81%). The effectiveness of the assessments was confirmed by an 83% student mastery rate, which is classified as "very effective." Consequently, the comic-based learning media developed through the 4-D model is regarded as highly suitable for utilization as a supportive instructional resource in the classroom.